The development of an instrument to assess primary school mathematics teachers’ values in teaching fractions / Jeyasingam Govindaraj - Jeyasingam, Govindaraj (2017)
The purpose of the study was to develop an instrument for assessing primary school mathematics teachers’ values in teaching fractions. There are few instruments available for assessing mathematics teachers’ values. This study was guided by the theory universal integrated perspective. Respondents were selected using the purposeful sampling method. Items were generated based on the analysis of literature and relevant documents. The initial instrument items were tested for content validity and refined through the focus group feedback, experts’ panel consensus, and pilot study. The pilot study was conducted on 150 national primary school mathematics teachers in Kuala Lumpur. The refined scale contained 36 items organised into three sub-constructs and nine dimensions. The selfreport perception questionnaire was used in the real study, conducted on 250 primary school mathematics teachers in Kuala Lumpur, using a 5- point Likert scale. Both the pilot study and real study results analysis determined the unidimensionality of the items and goodness of fit. Internal consistency, item reliability, and construct reliability of the instrument were determined by Rasch analysis, exploratory factor analysis and Confirmatory factor analysis. The one-way Analysis of Variance showed that the demographic factors except the teaching experience did not show a significant difference in the respondents’ scores. This developed instrument may be used by the curriculum developers, educators, textbook writers, researchers and preservice teachers looking for appropriate outcomes through the implementation. The study provides a starting point for further research on values assessment and values development for other mathematics topics in primary schools and secondary schools.